Quantitative Trait Relationship Modelling for Yield and Biofortification Traits in Rice (Oryza sativa L.) - Usharani G; Neeraja C N; Nagesh P; Ramya R; Hemanth K R M; Madhubabu P; Rao D S; Babu V R; Bharathi M; Rani CH V D (The Bioscan, 2013)
The present investigation was undertaken to estimate the direct and indirect effects of yield contributing, grain quality and biofortification traits on grain yield through path coefficient analysis in the rice cross Swarna × Madhukar. Six generations namely P₁, P₂, F₁, F₂, BC₁ and BC₂ were evaluated during kharif 2012 under irrigated conditions at DRR Farm, ICRISAT campus, Hyderabad. Observations were recorded for plant height, days to 50% flowering, panicle length, productive tillers per plant, filled grains per panicle, test weight, kernel dimensions, grain iron content, grain zinc content and grain yield per plant. Path coefficient analysis revealed that productive tillers per plant exerted the highest positive direct effect on grain yield followed by filled grains per panicle and test weight, indicating their major contribution toward productivity. Zinc content also exhibited positive direct influence on yield, suggesting the possibility of simultaneous improvement of productivity and nutritional quality. In contrast, panicle length, kernel traits and iron content recorded negative direct effects on yield. The residual effect (0.4186) indicated that the studied traits contributed substantially toward grain yield variation. The results suggest that emphasis on productive tillers per plant, filled grains per panicle and test weight would be effective for identifying superior high yielding and nutritionally improved rice genotypes.